Weaponizing Sovereignty: Hungary’s Protection of National Sovereignty Act and the Erosion of Fundamental Rights - Setyo Widagdo; Fransiska A. Susanto; Anak Agung Ayu Nanda Saraswati (Jurnal Suara Hukum, 2026)
On November 21, 2023, Hungarian Prime Minister Viktor Orban, leader of the Fidesz Party, submitted Act LXXXVIII of 2023 on the Protection of National Sovereignty to fight what he described as unwarranted political intervention by foreigners or specialised organisations. The SPO's major task is to "protect the constitutional identity," as outlined in Article R(4) of the Fundamental Law, through the implementation of proposal, investigation, analyses, and assessment in accordance with the law. The European Commission has stated that Hungary's sovereignty law contravenes several EU regulations, including those concerning EU citizens' voting rights, personal data protection, freedom of association, the right to an effective remedy, and the right to a fair trial. This article uses normative legal research methodology or doctrinal legal research to examine Hungary’s approach to sovereignty protection and its interpretation under international law. The analysis demonstrates that .